Hydrogenated Amorphous Silicon Density of State Analyzed by Dielectric Function Model Derived from Ellipsometric Spectroscopy - Yoyok Cahyono; Soni Prayogi; Darminto Darminto (JPSE (Journal of Physical Science and Engineering), 2022)
In this study, we report the application of a functional dielectric model of scalable ellipsometric spectroscopy to investigate the optical response of materials in the optical spectrum modeling of hydrogenated amorphous silicon. ES is used to obtain the dielectric constant of the data fitting experimental. Then ψ and Δ are obtained from the analysis of the experimental comparison of the valence band and the conduction band state density with the band structure theory for a-Si: H. The analysis results are that for a-Si: H, the density of state model for all electronic transitions is obtained, whose results are consistent with experimental data from ES measurements over the entire photon energy range of 0.5–6.5 eV. Our results demonstrate the high-energy excitons and plasmons for the performance of photovoltaic devices in a-Si: H. Overall, we believe our methodology can study in detail about electron and hole interactions in semiconductors.DOI: 10.17977/um024v7i22022p068